THE EFFECTIVENESS SMART APPS CREATOR LEARNING MEDIA IMPROVING STUDENT LEARNING OUTCOMES IN THE ERA OF THE COVID-19 PANDEMIC - Herlan Perdana Putra; Elsje Theodora Maasawet; Muh. Amir Masruhim (Program Pascasarjana Universitas Negeri Jakarta, 2021)
This study aims to design learning media smart Apps Creator, validity, practicality, and effectiveness on student learning outcomes using learning media Smart Apps Creator Android. This type of research is research and development (R&D) with the DDD-E development model. The output produced is the